Forces Governing the Transport of Pathogenic and Nonpathogenic Escherichia coli in Nitrogen and Magnesium Doped Biochar Amended Sand Columns - Katherine Quinn; Sohrab Haghighi Mood; Elizabeth Cervantes; Manuel Garcia Perez; Nehal I. Abu-Lail (Microbiology Research, 2023)
Background: Access to safe drinking water remains a global issue with fecal indicator bacteria being major pollutants. Biochars offer low-cost adsorbents for bacterial pathogens. A fundamental understanding of how biochars interact with bacterial pathogens is essential to designing effective biofilters. Methods: Water-saturated sand columns amended with Magnesium and Nitrogen-doped biochars produced by pyrolysis at 400, 500, 600, and 700 °C were used to Quantify the transport of pathogenic Escherichia coli O157:H7 and nonpathogenic E. coli k12 strains in porous media. Measured data were modeled using DLVO theory of colloidal stability. were explored. Results: (1) Biochar is hydrophobic while sand and bacteria are hydrophilic; (2) all Gibbs free energy values quantified between E. coli O157:H7 and biochar were negative except for biochar produced at 700 °C; (3) all types of forces investigated (van der Waals, electrostatic, and acid-base interactions) played a role in governing the interactions between bacteria and biochar. Conclusions: (1) Adding doped biochar to sand at a 2% weight ratio enhanced the retention of bacterial cells in the sand/biochar columns; (2) bacterial transport is strain-dependent and mediated by various types of forces resulting from interactions between the various functional groups displayed on bacteria and biochar/sand. Our findings emphasize the importance of monitoring biochar’s functionality to eliminate bacterial pollutants from contaminated water.